Children’s Dentistry The Impact of Pediatric Medications on Oral Development - Theyab Ali S Abuhasharah, Najah hassan asiri, Naif A Alasmari, Alhanouf Nasser Asiri, Mosa Ali Asiri, Mohammad Alhasan Suhail, Saeed Ali Alzain, Mohammed Alhassn Almughaidi, Mofareh Mousa Abdullah Al Nasser (Journal of International Crisis and Risk Communication Research, 2024)
Pediatric medications play a crucial role in managing various childhood illnesses, but they can also significantly impact oral development and dental health. Medications such as antibiotics, antihistamines, and corticosteroids are commonly prescribed for children, yet their side effects may include alterations in oral flora, dry mouth, and changes in taste sensation. These conditions can lead to an increased risk of dental caries and gum disease, highlighting the need for careful consideration by pediatricians and dentists when prescribing and administering these treatments. The timing and method of medication delivery, such as liquid formulations often containing sugar, can also contribute to enamel erosion and cavities if oral hygiene practices are not adequately reinforced. Furthermore, long-term use of certain medications can affect the development of permanent teeth and jaw structure. For instance, some medications may disrupt normal bone growth or alter the eruption patterns of teeth, which can lead to misalignment and the need for orthodontic intervention later on. It’s vital for healthcare professionals to collaborate on a child's treatment plan, ensuring that parents are educated about the potential oral health implications of medications. Regular dental check-ups become essential during this time, allowing for early detection and management of any developing issues.